Prognosis of Intraventricular Hemorrhage - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
The relationship of periventricular-intraventricular hemorrhage in infants of <32 weeks gestation to the occurrence of disability at 5 years of age was studied in a National Collaborative Survey in the Netherlands.